A content analysis of selected research studies on rural development in Thailand, 1977-1985 - Ploenchan Akevanich (1986)
This study is the first attempt to compile a bibliography of selected research studies on rural development in Thailand, with complete bibliographic information, descriptors, availability of each title, abstract, and various indices, together with the content analysis of all listed titles. It is intended to serve primarily rural development researchers, administrators, policy-makers, and instructors. It is also intended to enable them to locate the relevant information on rural development of the country, as well as to identify the gaps in the research studies in terms of subject and geographic areas. The bibliography is limited to research studies published during 1977-1985.